25x-6=40x+6

Simple and best practice solution for 25x-6=40x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25x-6=40x+6 equation:


Simplifying
25x + -6 = 40x + 6

Reorder the terms:
-6 + 25x = 40x + 6

Reorder the terms:
-6 + 25x = 6 + 40x

Solving
-6 + 25x = 6 + 40x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-40x' to each side of the equation.
-6 + 25x + -40x = 6 + 40x + -40x

Combine like terms: 25x + -40x = -15x
-6 + -15x = 6 + 40x + -40x

Combine like terms: 40x + -40x = 0
-6 + -15x = 6 + 0
-6 + -15x = 6

Add '6' to each side of the equation.
-6 + 6 + -15x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + -15x = 6 + 6
-15x = 6 + 6

Combine like terms: 6 + 6 = 12
-15x = 12

Divide each side by '-15'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| -65(y-79)=y+98 | | 9x-3x=54 | | -p=8p-18 | | 7+29x=42+22x | | 10+4f=-34 | | -7x^2+23x+20=0 | | 7n=3n-40 | | 4x-2(x-5)=4x+6 | | 3y-5=-8 | | L=7nr | | 7/3+4y=8y-1/3 | | 4x+6=3x-4 | | 1x^2+8x+6=0 | | 1x^2+8x+14=0 | | 7(3x-13)=224 | | 9+12n-1=9n+26-3n | | m+(m+2)+(m+4)=72 | | 9x+7=12x-5 | | 4c-3=2c+5 | | (x-8)(x+3)= | | 64-7k=-11k+8 | | -3x^2+19x-28=0 | | 2x^2+22x-48=0 | | -(5-t)=0[37t-12t+5(14+3t)] | | 2x^2+12=18 | | a+65=5a-15 | | 3(5w+15)=210 | | 5x-8y=1 | | f(1-2)= | | 5(x+3)=2(x+1) | | a-9a+75=135+2a | | -6z+8+4z=-3z+13 |

Equations solver categories